Cardiovascular Abnormalities and Mental Health Difficulties Result in a Reduced Quality of Life in the Post-Acute COVID-19 Syndrome - Catalina Giurgi-Oncu (MDPI AG, 2021)
(1) Background: Post-acute COVID-19 syndrome, characterized by persisting symptoms up to 12 weeks after the acute illness, impairs numerous people’s physical and mental health. (2) Methods: 64 inpatients and 79 outpatients, aged under 55 years, with post-acute COVID-19, were evaluated by a transthoracic echocardiography (TTE), mental health examination, Quality of Life (QoL) questionnaire, post-COVID-19 functional status scale (PCFS) and Hospital Anxiety and Depression Scale (HADS). (3) Results: all inpatients had mild/moderate pulmonary injury during acute COVID-19, in contrast to 37.97% of outpatients. Inpatients who reported an average of 5 persisting symptoms, had, predominantly, level 3 PCFS and a median QoL of 62, compared to outpatients, who reported an average of 3 symptoms, level 1 PCFS and a median QoL score of 70. Increased pulmonary artery pressure was detected in 28.11% of inpatients, compared to 17.72% of outpatients, while diastolic dysfunction was diagnosed in 28.12% of inpatients, in comparison with 20.25% of outpatients (p = 0.02). Abnormal systolic function was assessed in 9.37% of inpatients, and 7.58% of outpatients. According to the HADS depression subscale, 46.87% of inpatients and 27.84% of outpatients had clinical depression. Concomitantly, anxiety was detected in 34.37% of inpatients and 40.5% of outpatients (4) Conclusions: cardiovascular and mental health difficulties were frequently detected in patients with post-acute symptoms of COVID-19, which correlated with the number and intensity of persisting symptoms and reduced QoL scores.